TACTICS OF PREPARING STUDENTS FOR PEDAGOGICAL ACTIVITY - Tolipova Ozoda Ikromovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article highlights that the preparation of Students for pedagogical activity in pedagogical higher educational institutions is a complex process, the rational implementation of which serves to ensure the professional maturity of the future pedagogical staff.